Regeneration method of waste graphite negative electrode material

By using composite additives to perform two-stage calcination and acid treatment on the graphite anode materials of waste lithium-ion batteries, the problem of difficult recycling of graphite anode materials of waste lithium-ion batteries is solved, and efficient resource regeneration and electrochemical performance improvement is achieved.

CN115498185BActive Publication Date: 2025-05-02GUANGXI CHENYU NEW MATERIALS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211148893.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-21
Publication Date
2025-05-02
Estimated Expiration
2042-09-21

AI Technical Summary

Technical Problem

The graphite negative electrode materials in waste lithium-ion batteries are difficult to efficiently recycle and reuse, resulting in waste of valuable resources and environmental pollution.

Method used

The composite additives containing components A and B are used for two-stage calcination, and the graphite negative electrode material is separated by acid treatment to repair the damaged structure, retain the electrochemical beneficial components, and reduce the undesirable components.

Benefits of technology

It effectively improves the electrochemical performance of recycled graphite anode materials, improves regeneration and recovery, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115498185B_ABST
    Figure CN115498185B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of negative electrode recycling, and particularly relates to a regeneration method for waste graphite negative electrode materials. A mixture containing waste graphite negative electrode materials and a composite auxiliary agent is subjected to two-stage roasting treatment; wherein, the composite auxiliary agent includes component A and component B; component A is a salt containing NH4 + salt; component B includes iron oxides; during the two-stage roasting process, the temperature of the first-stage roasting is 650-900 °C; the temperature of the second-stage roasting is 1500-2000 °C; the roasted product is subjected to acid treatment to separate and obtain graphite negative electrode materials. Under the combined one-pot two-stage roasting described in the present invention, synergism can be unexpectedly achieved, which can significantly improve the performance of the regenerated graphite and also help to improve the regeneration recovery rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of recycling waste battery materials, and in particular to the field of recycling waste graphite materials. Background Art

[0002] Lithium-ion batteries have been widely used in various fields due to their many advantages such as high energy density, long service life and good safety. However, this has also led to an increase in the amount of lithium-ion battery scrap and the problem of the reasonable disposal of waste lithium-ion batteries. Because waste lithium-ion batteries contain a large amount of valuable metals such as lithium and cobalt, they are regarded as important secondary resources. The current research hotspot is still focused on the recycling of high-value positive electrode materials of waste lithium-ion batteries. Since the added value of negative electrode materials is lower than that of positive electrode materials containing a large amount of precious metals, there are few studies on the recycling of negative electrode materials of waste lithium-ion batteries. Most companies treat waste graphite powder as solid waste, which not only wastes valuable resources, but also easily causes environmental pollution.

[0003] The negative electrode materials used in commercial lithium-ion batteries are generally artificial graphite or natural graphite. Natural graphite is formed from natural graphite ore through natural processes, and requires preliminary purification, shaping, modification and other processes to obtain graphite negative electrode materials that meet the requirements of use; artificial graphite needs to undergo a high temperature process above 2500°C to graphitize the soft carbon material, and obtain a graphite negative electrode material with better surface properties and better cycle stability. Whether it is natural graphite or artificial graphite, it is necessary to select specific carbonaceous raw materials, go through complex processing procedures, and consume a lot of resources and energy to obtain it. Realizing its full and high-quality recovery is of great significance for the recycling of resources.

[0004] However, the long-term cycle process during the battery's service life changes the original surface properties and crystal structure of graphite, reducing its electrochemical properties such as reversible specific capacity, first coulomb efficiency and cycle life. The graphite powder obtained from the disassembly and physical sorting of waste lithium-ion batteries is more complex in composition. It not only contains the main component graphite, but also contains some positive electrode powder, aluminum foil, copper foil and a small amount of diaphragm, electrolyte components, etc., making it difficult to recycle and reuse waste graphite negative electrode powder. Faced with the surge in the number of waste lithium-ion batteries, how to effectively recycle the relatively high proportion of waste lithium-ion battery graphite negative electrodes and realize their reuse is an urgent problem to be solved. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for regenerating waste graphite negative electrode materials (also called retired graphite negative electrode materials), aiming to obtain graphite negative electrode active materials with excellent electrochemical properties based on the regeneration of retired graphite negative electrode materials.

[0006] In view of the damaged structure of waste graphite negative electrode materials, how to effectively repair the damaged structure is one of the difficulties in improving the performance of the regenerated graphite negative electrode. In addition, there is an SEI film layer on the surface of the graphite negative electrode, and there are certain beneficial doping components and electrochemically unhelpful components introduced by the cycle. How to selectively retain the beneficial components and effectively transform the unhelpful components is another difficulty in improving the performance of the regenerated negative electrode. In view of the problem that waste graphite negative electrode materials are difficult to regenerate, the regenerated carbon rate is not high, and the electrochemical performance of the regenerated materials is not ideal, the present invention provides the following solutions:

[0007] A method for regenerating waste graphite negative electrode materials, comprising the steps of:

[0008] Step (1):

[0009] The mixture containing waste graphite negative electrode material and composite additive is subjected to two-stage roasting treatment;

[0010] Wherein, the composite auxiliary agent comprises component A and component B;

[0011] The component A comprises NH4 + Salt; said component B comprises iron oxide;

[0012] In the two-stage roasting process, the temperature of the first stage is 650-900°C; the temperature of the second stage is 1500-2000°C;

[0013] Step (2):

[0014] The product of step (1) is treated with acid to separate and obtain graphite negative electrode material.

[0015] The present invention innovatively performs two-stage calcination of the graphite negative electrode in the presence of a composite auxiliary agent comprising component A and component B, and further based on the joint control of the composite auxiliary agent components, the two-stage calcination temperature mechanism and the acid treatment, can achieve synergy and effectively repair the damaged structure. In addition, it can also highly selectively retain the electrochemical beneficial components and highly selectively reduce the unhelpful components, thereby synergistically improving the electrochemical properties of the treated material, and in addition, it also helps to improve the regeneration recovery rate.

[0016] In the present invention, the waste graphite negative electrode material is a negative electrode material obtained by stripping a negative electrode sheet.

[0017] Preferably, the waste graphite negative electrode material is a negative electrode material obtained by peeling off a negative electrode sheet of a lithium secondary battery.

[0018] In the present invention, the waste graphite negative electrode material mainly comprises graphite, and in addition, a conductive agent, a binder and trace components are also allowed to exist.

[0019] Preferably, in the waste graphite negative electrode material, the content of graphite is greater than or equal to 80wt%.

[0020] In the present invention, the combined auxiliary two-stage roasting of the special components A and B is the key to synergistically achieving the structural repair of waste graphite materials, regulating electrochemical beneficial components, improving the electrochemical properties of recycled materials and improving the regeneration carbon yield.

[0021] In the composite auxiliary agent, the component A includes at least one of component A-1 and component A-2; wherein component A-1 is one or more of ammonium fluoride, ammonium chloride, ammonium sulfate, ammonium hydrogen sulfate, ammonium carbonate, ammonium hydrogen carbonate, and ammonium nitrate; component A-2 is one or more of ammonium molybdate, ammonium citrate, diammonium citrate, ammonium oxalate, and ammonium carbamate;

[0022] More preferably, the component A is component A-1 and component A-2, and the molar ratio of the two is preferably 1:0.5 to 2, and more preferably 1:1 to 1.5. The study unexpectedly found that the combination of components A-1 and A-2 can further achieve synergy, obtain better performance of the recycled material, and improve the regeneration carbon rate.

[0023] More preferably, the component A is a mixture of ammonium citrate and ammonium chloride, and the molar ratio of the two is preferably 1:1-2.

[0024] Preferably, in the composite auxiliary agent, in the component B, the iron oxide phase is at least one of FeO and Fe2O3;

[0025] Preferably, the component B also contains at least one of nickel oxide and copper oxide. The present invention has found that further adding auxiliary nickel and copper oxides on the basis of the iron oxide can help to further improve the combined synergistic effect of components A and B, and help to further improve the electrochemical properties and regeneration recovery rate of the regenerated material.

[0026] Preferably, component B includes a combination of iron oxide and nickel oxide; the present invention has found that by using the preferred combination, better regenerative electrochemical performance can be unexpectedly obtained.

[0027] Preferably, in component B, the content of iron oxide is greater than or equal to 50 wt.%, preferably 60 to 80 wt.%.

[0028] Preferably, in the composite auxiliary agent, the weight ratio of component A to component B is 1:0.1-10, preferably 1:0.5-2.

[0029] In the present invention, the waste graphite negative electrode material and the composite auxiliary agent can be mixed based on existing means. Preferably, in the present invention, the waste graphite negative electrode material and the composite auxiliary agent are kneaded and pressed to obtain the mixture;

[0030] Preferably, the temperature of the kneading process is 60-80°C, the kneading power is 7-15kW, and the kneading time is 10-30min;

[0031] Preferably, in the mixture, the weight content of the composite auxiliary agent is 2 to 20 wt%, preferably 6 to 20 wt%;

[0032] Preferably, the atmosphere in the two-stage roasting treatment stage is a protective atmosphere; in the present invention, the protective atmosphere is, for example, at least one of nitrogen and an inert gas.

[0033] Preferably, the temperature of the first stage calcination is 650-800°C, more preferably 650-700°C.

[0034] Preferably, the first stage of roasting takes 1 to 3 hours;

[0035] Preferably, the temperature of the second stage calcination is 1800-2000°C.

[0036] Preferably, the second calcination time is 2 to 8 hours, preferably 2 to 5 hours.

[0037] In the present invention, the product treated in step (1) is cooled and then subjected to acid treatment.

[0038] Preferably, in step (2), the acid treatment is carried out in a solution containing hydrogen peroxide and an inorganic acid. The present invention has found that the use of hydrogen peroxide-assisted acid treatment helps to further cooperate with the process of step (1) and helps to further improve the electrochemical properties of the regenerated graphite material.

[0039] Preferably, the inorganic acid is at least one of hydrochloric acid, nitric acid and hydrofluoric acid, wherein the concentration of the acid is 1 to 8 M, preferably 2 to 7 M;

[0040] Preferably, in the acid-treated solution, the inorganic acid is a ternary composite acid comprising hydrochloric acid, nitric acid and hydrofluoric acid; wherein the concentration of hydrofluoric acid is 1-2 mol / L, the concentration of hydrochloric acid and nitric acid is 2-4 mol / L, the pickling temperature is 40-60°C, and the amount of hydrogen peroxide added is 0.01-0.5 mol / L. The present invention also unexpectedly found that under the hydrogen peroxide-assisted ternary acid treatment process, the composition of the regenerated material can be further coordinated and regulated, which helps to further coordinately improve the electrochemical performance of the regenerated negative electrode.

[0041] Preferably, in the acid-treated solution, the concentration of hydrogen peroxide (in terms of H2O2) is 0.01-0.5 mol / L, preferably 0.1-0.5 M;

[0042] Preferably, the acid treatment time is 1 to 3 hours.

[0043] The regeneration method of the present invention further comprises step (3): coating the graphite negative electrode material obtained in step (2) with a carbon source to obtain a carbon-coated precursor, and then carbonizing the carbon-coated graphite negative electrode material to obtain an amorphous carbon-coated graphite negative electrode material. The present invention has found that the combined modification of steps (1-2) and the further use of amorphous carbon coating methods can help further improve the performance of the regenerated graphite.

[0044] Preferably, the weight ratio of the treated product in step (2) to the carbon source is 10 to 50:1, preferably 20 to 30:1;

[0045] In the present invention, the carbon source coating and carbonization can be performed based on existing means.

[0046] Preferably, the carbon source is asphalt with a softening point of 65 to 90°C;

[0047] Preferably, in step (3), the graphite negative electrode material obtained in step (2) is mixed with a carbon source in a molten state, and treated under negative pressure in advance, and then treated under positive pressure, and then cooled and solidified to obtain a carbon-coated precursor. The present invention has found that the use of a negative pressure-positive pressure variable pressure treatment process is helpful to further facilitate the structural repair of waste graphite and to further synergistically improve the performance of the regenerated graphite material.

[0048] Preferably, the temperature during the negative pressure and positive pressure treatment process is 150-200°C;

[0049] Preferably, the negative pressure is less than or equal to 80 mbar, and the positive pressure is 0.1-0.5 Mpa;

[0050] Preferably, the holding time of negative pressure and positive pressure is 5-10 minutes respectively.

[0051] Preferably, in step (3), carbonization is carried out under a protective atmosphere;

[0052] Preferably, the carbonization temperature is 1000-1300°C, preferably 1100-1200°C.

[0053] Preferably, the carbonization time is 3 to 6 hours.

[0054] A preferred processing method of the present invention comprises the following steps:

[0055] Step 1: Mix the waste graphite negative electrode material and the combined additive (component A and component B) in proportion, then add water to mix and shape, and dry at 80-120°C to obtain a molding material;

[0056] The recycled carbon powder is a carbonaceous powder with graphite as the main component obtained by crushing, disassembling and sorting waste lithium-ion batteries; the component A is one or more of ammonium fluoride, ammonium chloride, ammonium sulfate, ammonium hydrogen sulfate, ammonium carbonate, ammonium hydrogen carbonate, ammonium nitrate, ammonium molybdate, ammonium citrate, diammonium citrate, ammonium oxalate and ammonium carbamate; the component B is at least one of iron oxide, nickel oxide or copper oxide; the mass ratio of the recycled carbon powder, component A and component B is 80-98:1-10 : 1-10; the kneading is carried out in a kneading machine, preferably a continuous kneading machine, so that the above materials are paste-like and mixed evenly, the kneading temperature is 60-80 ° C, the kneading power is 7-15kW, and the kneading time is 10-30min; the molding can be vibration molding, extrusion molding, compression molding, isostatic pressing, preferably a sliding table vibration molding machine, the amplitude is 0.5-1.5mm, the molding pressure is between 0.04-0.06MPa, and the molding time is 80-100s;

[0057] Put the molding material into a roasting furnace, slowly heat it to 650-900℃ under the protection of inert atmosphere, keep it warm for 1-3h, then continue to heat it to 1500-2000℃, keep it warm for 2-8h, and naturally cool it to obtain the roasting material;

[0058] Step 2: The roasted material is subjected to a combined acid treatment under the assistance of hydrogen peroxide, and then washed and dried to obtain an acid-treated material; the acids used are hydrochloric acid, nitric acid and hydrofluoric acid, the concentration of hydrofluoric acid is 1-2 mol / L, the concentration of hydrochloric acid and nitric acid is 2-4 mol / L, the pickling temperature is 40-60°C, the amount of hydrogen peroxide added is 0.01-0.5 mol / L; the pickling time is 1-3h;

[0059] Step 3: crush and classify the acid-treated material in a crusher to obtain a powder with a particle size of 10-20 μm; perform carbon coating modification on the classified powder, melt the medium-temperature asphalt at 150-200°C, uniformly mix the graphitized material and the molten asphalt, the mass ratio of the graphitized material to the asphalt is 10-50:1, perform negative pressure treatment, then perform positive pressure treatment, and then cool to room temperature, and finally perform high-temperature carbonization at 1000-1300°C, preferably above 1100-1200°C, under an inert atmosphere for 3-6 hours to obtain the artificial graphite negative electrode; the medium-temperature asphalt is petroleum asphalt or coal tar asphalt, and the softening point is 65-90°C; the inert atmosphere is nitrogen or argon atmosphere.

[0060] The beneficial effects of the technical solution of the present invention are:

[0061] (1) The present invention innovatively discovered that the graphite negative electrode is subjected to two-stage roasting in the presence of a composite auxiliary agent comprising component A and component B, and further based on the combined control of the composite auxiliary agent composition, the two-stage roasting temperature mechanism and the acid treatment, synergy can be achieved, and the damaged structure can be effectively repaired. In addition, the electrochemical beneficial components can be highly selectively retained, and the unhelpful components can be highly selectively reduced, thereby synergistically improving the electrochemical performance of the treated material. In addition, it also helps to improve the regeneration recovery rate.

[0062] (2) The use of a combination of component A-1 and component A-2 as component A can further improve its combined synergy with component B and the two-stage roasting process and conditions. In addition, the use of a combination of iron oxide and nickel oxide as component B can also unexpectedly further have a combined synergistic effect with component A. In the present invention, the use of a combination of components A and B can further improve the electrochemical properties of the regenerated graphite and help improve the carbon yield.

[0063] (2) Under the two-stage roasting innovation assisted by the composite additive, further combined with the ternary composite acid treatment assisted by hydrogen peroxide, it helps to further synergistically improve the electrochemical properties of the regenerated graphite;

[0064] (3) Coating the acid-treated components with amorphous carbon, especially using the voltage-switching coating process, helps to further synergistically improve the electrochemical performance of the regenerated negative electrode.

[0065] (4) The process of the present invention can prepare materials with high electrochemical properties based on the resource utilization of waste materials and has excellent market value. In addition, the processing process is simple, easy to operate, easy to achieve large-scale production, and has good prospects for practical application. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 , 2 This is a SEM image of the regenerated graphite material of Example 1, wherein: Figure 2 It is a high magnification image;

[0067] Figure 3 This is the electrochemical performance diagram of the regenerated graphite material of Example 1; DETAILED DESCRIPTION

[0068] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.

[0069] In each embodiment and comparative example of the present invention, the recycled carbon powder is a carbonaceous powder with graphite as the main component obtained by crushing, disassembling and sorting the graphite negative electrode sheets of waste lithium-ion batteries, and the carbon content is 92wt%. The recovery rate of the regenerated artificial graphite is calculated based on the carbon content.

[0070] Electrochemical performance test: The graphite electrode (the weight ratio of graphite active material, acetylene black and PVDF is 90:5:5) was used as the working electrode, metallic lithium was used as the negative electrode, 1 mol / L LiPF6 EC / EMC (volume ratio 1:1) was used as the electrolyte, and the PE-PP composite film was used as the separator. CR2025 button cells were assembled in a dry glove box filled with argon, and the battery charge and discharge tests were performed at room temperature (25°C) in the voltage range of 0.001-1.8V and at a rate of 0.2C.

[0071] In the following cases, unless otherwise stated, the heating rate is 2°C / min.

[0072] Example 1

[0073] Step (1):

[0074] The recycled carbon powder, ammonium citrate (component A), iron oxide (component B1), and nickel oxide (component B2) are mixed uniformly in a mass ratio of 94:3:2:1, and then put into a continuous kneading machine, add water and knead, the kneading temperature is 70°C, the kneading power is 10kW, and the kneading time is 20min; then the kneaded material is put into a vibration molding machine for molding treatment, the amplitude is 1mm, the molding pressure is between 0.05MPa, and the molding time is 90s; finally, it is dried at 105°C to obtain a molding material;

[0075] Step (2):

[0076] The molding material is placed in a calcining furnace, and the temperature is slowly raised to 800°C (T1) under the protection of a nitrogen atmosphere, and kept at this temperature for 2 hours, and then the temperature is further raised to 1800°C (T2), and kept at this temperature for 4 hours, and the calcined material is obtained after natural cooling;

[0077] Step (3):

[0078] The calcined material is placed in a composite acid solution containing hydrogen peroxide, HF, HCl and HNO3, and the composite acid treatment is performed under the condition of hydrogen peroxide assistance. In the composite acid solution, the concentration of hydrofluoric acid is 1 mol / L, the concentration of hydrochloric acid is 3 M, the concentration of nitric acid is 1 mol / L, and the concentration of hydrogen peroxide (in terms of H2O2) is 0.1 M;

[0079] The acid treatment temperature is 50°C and the acid treatment time is 2h; then washing and drying are performed to obtain the acid-treated material;

[0080] Step (4):

[0081] The acid-treated material is crushed and graded in a crusher to obtain a powder with a particle size of 15 μm, and then carbon-coated and modified. The medium-temperature coal tar pitch with a softening point of 80°C is melted at 160°C. In a vacuum tank, the graphitized material and the molten asphalt are evenly mixed. The mass ratio of the graphitized material to the asphalt is 20:1. The pressure is evacuated to 80 mbar and maintained for 8 minutes. Then, the pressure is pressurized to 0.5 MPa through the atmosphere and maintained for 5 minutes, and then cooled to room temperature. The material is carbonized at a high temperature of 1150°C for 3 hours in a nitrogen atmosphere to obtain the regenerated artificial graphite negative electrode.

[0082] The recovery rate of regenerated artificial graphite is 90%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 344 mAh / g and the first coulombic efficiency was 95%.

[0083] Example 2

[0084] Compared with Example 1, the only difference is that the component A of the combined auxiliary agent is changed, and ammonium chloride is used as component A, and its addition amount relative to graphite is the same as that of Example 1;

[0085] The recovery rate of regenerated artificial graphite is 92%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 351 mAh / g and the first coulombic efficiency was 94%.

[0086] Example 3

[0087] Compared with Example 1, the only difference is that the component A of the combined auxiliary agent is changed, and ammonium citrate and ammonium chloride are used as component A, and the molar ratio thereof is 1:1, and the addition amount of graphite is the same as that of Example 1;

[0088] The recovery rate of regenerated artificial graphite is 93%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 358 mAh / g and the first coulombic efficiency was 96%.

[0089] By comparing Examples 1 and 2, it can be seen that the use of combined component A can unexpectedly achieve a synergistic effect, which can further improve the regeneration recovery rate and the electrochemical performance of the regenerated material.

[0090] Example 4

[0091] Compared with Example 1, the only difference is that the component B of the combined auxiliary agent is changed to:

[0092] Group 1: Ferrous oxide and cupric oxide are used as component B in a molar ratio of 3:2. The addition amount of graphite is the same as that in Example 1. Other operations and parameters are the same as those in Example 1.

[0093] Group 2: Only iron oxide is used as component B, and the amount of component B remains unchanged; other operations and parameters are the same as in Example 1.

[0094] The results of the assay according to Example 1 are as follows:

[0095] Group 1: The recovery rate of regenerated artificial graphite is 91%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 343mAh / g and the first coulombic efficiency was 93%.

[0096] The second group: The recovery rate of regenerated artificial graphite was 88%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 340mAh / g and the first coulombic efficiency was 89%.

[0097] By comparing Examples 1 and 4, it can be seen that the use of a special combination of component B can unexpectedly achieve synergy and obtain better regeneration recovery rate and regeneration electrochemical performance.

[0098] Example 5

[0099] Compared with Example 1, the only difference is that the composition ratio of the combined auxiliary agent and the addition amount of graphite are changed, and the carbon powder, ammonium citrate, iron oxide and nickel oxide are recycled in a ratio of 80:10:6:4.

[0100] The recovery rate of regenerated artificial graphite is 86%. The electrochemical performance of the prepared artificial graphite material product is tested. At a rate of 0.2C, the first reversible capacity is 350 mAh / g and the first coulombic efficiency is 92%.

[0101] Example 6

[0102] Compared with Example 1, the only difference is that the temperature of the second stage calcination in step (1) is changed: slowly heating to 650° C. under nitrogen atmosphere protection, keeping the temperature for 3 h, then continuing to heat to 2000° C., keeping the temperature for 2 h, and naturally cooling to obtain the calcined material;

[0103] The recovery rate of regenerated artificial graphite is 87%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 354 mAh / g and the first coulombic efficiency was 94%.

[0104] Example 7

[0105] Compared with Example 1, the only difference is that the acid solution composition of the acid treatment in step (3) is changed, and the different acid solution is a solution containing hydrogen peroxide, HF and HCl, the concentration of hydrofluoric acid is 1 mol / L, the concentration of hydrochloric acid is 4 mol / L, and the concentration of hydrogen peroxide (in terms of H2O2) is 0.1M; the other acid treatment processes are the same as in Example 1;

[0106] The recovery rate of regenerated artificial graphite is 88%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 339 mAh / g and the first coulombic efficiency was 92%.

[0107] Example 8

[0108] Compared with Example 1, the only difference is that the acid treatment components are changed: respectively:

[0109] Group 1: In the acid solution, the concentration of hydrofluoric acid is 2 mol / L, the concentration of hydrochloric acid and nitric acid is 1 mol / L, the concentration of hydrogen peroxide is 0.1 M, and the other acid treatment processes are the same as those in Example 1;

[0110] Group 2: Compared with Example 1, the only difference is that no hydrogen peroxide is added to the acid solution, and other operations and parameters are the same as Example 1.

[0111] The structure was determined by the method of Example 1:

[0112] Group 1: The recovery rate of regenerated artificial graphite is 91%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 345mAh / g and the first coulombic efficiency was 93%.

[0113] The second group: The recovery rate of regenerated artificial graphite is 91%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 323mAh / g and the first coulombic efficiency was 88%.

[0114] Example 9

[0115] Compared with Example 1, the only difference is that the variable pressure carbon coating process in step 4 is changed: respectively:

[0116] Group 1:

[0117] The medium-temperature coal tar pitch with a softening point of 90°C was melted at 200°C, and the graphitized material and the molten asphalt were uniformly mixed in a vacuum tank, with the mass ratio of the graphitized material to the asphalt being 30:1. The pressure was evacuated to 60 mbar, maintained for 10 minutes, and then pressurized to 0.1 Mpa through the atmosphere, maintained for 10 minutes, and then cooled to room temperature. The other carbonization processes were the same as those in Example 1.

[0118] Group 2:

[0119] Compared with the first group, the only difference is that during the mixing process, there is no pre-negative pressure followed by positive pressure, but it is always under normal pressure.

[0120] The scheme of Example 1 was used for measurement, and the results were:

[0121] Group 1: The recovery rate of regenerated artificial graphite is 90%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 355mAh / g and the first coulombic efficiency was 94%.

[0122] The second group: The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 335 mAh / g and the first coulombic efficiency was 90%.

[0123] Example 10

[0124] The recycled carbon powder and ammonium citrate are mixed uniformly in a mass ratio of 94:3:2:1, and then put into a continuous kneading machine, add water and knead, the kneading temperature is 80°C, the kneading power is 7kW, and the kneading time is 10min; then the kneaded material is put into a vibration molding machine for molding, the amplitude is 0.5mm, the molding pressure is between 0.06MPa, and the molding time is 100s; finally, the molding material is dried at 105°C to obtain a molding material;

[0125] The molding material is placed in a roasting furnace, slowly heated to 800°C under the protection of nitrogen atmosphere, kept warm for 3 hours, then continued to heat to 1800°C, kept warm for 2 hours, and naturally cooled to obtain a roasted material; the roasted material is subjected to a composite acid treatment under the condition of hydrogen peroxide assistance, the hydrofluoric acid concentration is 1 mol / L, the hydrochloric acid and nitric acid concentrations are 3 mol / L, the acid treatment temperature is 60°C, the hydrogen peroxide addition amount is 0.5 mol / L; the acid treatment time is 1 hour; then washed and dried to obtain an acid-treated material;

[0126] The acid-treated material is crushed and graded in a crusher to obtain a powder with a particle size of 10 μm, which is then carbon-coated and modified. The medium-temperature coal tar pitch with a softening point of 80°C is melted at 160°C. In a vacuum tank, the graphitized material and the molten asphalt are evenly mixed. The mass ratio of the graphitized material to the asphalt is 20:1. The pressure is evacuated to 80 mbar and maintained for 8 minutes. The pressure is then pressurized to 0.5 MPa through the atmosphere and maintained for 5 minutes. The material is then cooled to room temperature. The material is carbonized at 1000°C for 6 hours in a nitrogen atmosphere to obtain the regenerated artificial graphite negative electrode.

[0127] The recovery rate of regenerated artificial graphite is 89%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 340 mAh / g and the first coulombic efficiency was 92%.

[0128] Comparative Example 1

[0129] Compared with Example 1, the only difference is that ammonium citrate as component A is missing and the total amount of modifier remains unchanged; for example, the recovered carbon powder is mixed with iron oxide and nickel oxide in a mass ratio of 94:4:2;

[0130] The recovery rate of regenerated artificial graphite is 81%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 245 mAh / g and the first coulombic efficiency was 78%.

[0131] Comparative Example 2

[0132] Compared with Example 1, the only difference is that the composite auxiliary agent lacking iron oxide and nickel oxide as component B and having the same total modifier amount as Example 1 is used: the recycled carbon powder and ammonium citrate are uniformly mixed in a mass ratio of 94:6;

[0133] The recovery rate of regenerated artificial graphite is 84%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 266 mAh / g and the first coulombic efficiency was 80%.

[0134] Comparative Example 3

[0135] Compared with Example 1, the only difference is that urea is used instead of ammonium citrate, and the total amount of the composite auxiliary agent is the same as that of Example 1: tetrabutylammonium chloride, iron oxide, and nickel oxide are mixed uniformly in a mass ratio of 94:3:2:1;

[0136] The recovery rate of regenerated artificial graphite is 85%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 243 mAh / g and the first coulombic efficiency was 77%.

[0137] Comparative Example 4

[0138] Compared with Example 1, the only difference is that cobalt oxide is used instead of iron oxide, and the total amount of the composite auxiliary agent is the same as that of Example 1: ammonium citrate, cobalt oxide, and nickel oxide are mixed uniformly in a mass ratio of 94:3:2:1;

[0139] The recovery rate of regenerated artificial graphite is 81%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 226 mAh / g and the first coulombic efficiency was 72%.

[0140] Comparative Example 5

[0141] Compared with Example 1, the only difference is that the one-pot combined treatment method of steps (1) and (2) is changed, for example, the different steps (1) and (2) are:

[0142] The recycled carbon powder and ammonium citrate are mixed in a ratio of 94:3 (the process is the same as in Example 1) in advance, and then slowly heated to 800°C (T1) under the protection of a nitrogen atmosphere, and kept warm for 2 hours. The calcined material is then kneaded and formed with iron oxide and nickel oxide (according to the ratio of 94:2:1 of the recycled carbon powder (the process is the same as in Example 1)), and then kept warm at 1800°C (T2) for 4 hours, and naturally cooled to obtain the calcined material; the subsequent steps are the same as steps (3) and (4).

[0143] The recovery rate of regenerated artificial graphite is 86%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 265 mAh / g and the first coulombic efficiency was 79%.

[0144] Comparative Example 6

[0145] Compared with Example 1, the only difference is that the calcination process in step (2) is changed to only a single-stage T2 calcination: the steps that are different are: placing the molding material in a calcination furnace, slowly heating it to 1800° C. under the protection of a nitrogen atmosphere, keeping the temperature for 4 hours, and naturally cooling it to obtain a calcined material;

[0146] The recovery rate of regenerated artificial graphite is 89%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 289 mAh / g and the first coulombic efficiency was 83%.

[0147] Comparative Example 7

[0148] Compared with Example 1, the only difference is that the calcination process in step (2) is changed: the molding material is placed in a calcining furnace, slowly heated to 500° C. under the protection of a nitrogen atmosphere, kept warm for 2 h, then continued to heat to 1300° C., kept warm for 4 h, and naturally cooled to obtain a calcined material;

[0149] The electrochemical performance of the prepared artificial graphite material product was tested, and at a rate of 0.2C, the first reversible capacity was 258 mAh / g and the first coulombic efficiency was 76%.

[0150] Comparative Example 8

[0151] Compared with Example 1, the only difference is that the calcination process in step (2) is changed: the molding material is placed in a calcining furnace, and the temperature is slowly raised to 1000° C. under the protection of a nitrogen atmosphere, and kept at this temperature for 2 h, and then the temperature is further raised to 2200° C., and kept at this temperature for 4 h, and the calcined material is obtained after natural cooling;

[0152] The recovery rate of regenerated artificial graphite is 78%. The electrochemical performance of the prepared artificial graphite material product was tested. At a rate of 0.2C, the first reversible capacity was 295 mAh / g and the first coulombic efficiency was 82%.

Claims

1. A method for regenerating waste graphite negative electrode materials, characterized in that the steps include: Step (1): The mixture containing waste graphite negative electrode material and composite additive is subjected to two-stage roasting treatment; Wherein, the composite auxiliary agent comprises component A and component B; The component A comprises NH4 + Salt; said component B comprises iron oxide; In the two-stage roasting process, the temperature of the first stage is 650-900°C; the temperature of the second stage is 1500-2000°C; Step (2): The product of step (1) is treated with acid to separate and obtain graphite negative electrode material.

2. The method for regenerating waste graphite negative electrode material according to claim 1, characterized in that: The waste graphite negative electrode material is a negative electrode material obtained by stripping a negative electrode sheet.

3. The method for regenerating waste graphite negative electrode material according to claim 2, characterized in that: The waste graphite negative electrode material is the negative electrode material obtained by stripping the negative electrode sheet of a lithium secondary battery.

4. The method for regenerating waste graphite negative electrode material according to claim 2, characterized in that: In the waste graphite negative electrode material, the content of graphite is greater than or equal to 80wt%.

5. The method for regenerating waste graphite negative electrode material according to claim 1, characterized in that: In the composite auxiliary agent, the component A includes at least one of component A-1 and component A-2; wherein component A-1 is one or more of ammonium fluoride, ammonium chloride, ammonium sulfate, ammonium hydrogen sulfate, ammonium carbonate, ammonium hydrogen carbonate, and ammonium nitrate; and component A-2 is one or more of ammonium molybdate, ammonium citrate, diammonium citrate, ammonium oxalate, and ammonium carbamate.

6. The method for regenerating waste graphite negative electrode material according to claim 5, characterized in that: The component A is component A-1 and component A-2; and the molar ratio of the two is 1:0.5-2.

7. The method for regenerating waste graphite negative electrode material according to claim 1, characterized in that: In the component B, the physical phase of the iron oxide is at least one of FeO and Fe2O3.

8. The method for regenerating waste graphite negative electrode material according to claim 7, characterized in that: The component B further comprises at least one of nickel oxide and copper oxide.

9. The method for regenerating waste graphite negative electrode material according to claim 8, characterized in that: Component B includes a combination of iron oxide and nickel oxide.

10. The method for regenerating waste graphite negative electrode material according to claim 9, characterized in that: In component B, the content of iron oxide is greater than or equal to 50 wt.%.

11. The method for regenerating waste graphite negative electrode materials according to claim 10, characterized in that: In component B, the content of iron oxide is 60 to 80 wt.%.

12. The method for regenerating waste graphite negative electrode materials according to claim 1, characterized in that: In the composite auxiliary agent, the weight ratio of component A to component B is 1:0.1-10.

13. The method for regenerating waste graphite negative electrode material according to claim 12, characterized in that: In the composite auxiliary agent, the weight ratio of component A to component B is 1:0.5-2.

14. The method for regenerating waste graphite negative electrode material according to claim 1, characterized in that: The waste graphite negative electrode material and the composite auxiliary agent are kneaded and pressed to obtain the mixture.

15. The method for regenerating waste graphite negative electrode material according to claim 14, characterized in that: The temperature of the kneading process is 60-80°C, the kneading power is 7-15kW, and the kneading time is 10-30min.

16. The method for regenerating waste graphite negative electrode materials according to claim 14, characterized in that: In the mixture, the weight content of the composite additive is 2~20wt%.

17. The method for regenerating waste graphite negative electrode materials according to claim 1, characterized in that: The atmosphere during the two-stage calcination treatment is a protective atmosphere.

18. The method for regenerating waste graphite negative electrode materials according to claim 1, characterized in that: The first roasting time is 1~3h.

19. The method for regenerating waste graphite negative electrode materials according to claim 1, characterized in that: The second roasting time is 2~8h.

20. The method for regenerating waste graphite negative electrode materials according to claim 1, characterized in that: In step (2), acid treatment is carried out in a solution containing hydrogen peroxide and an inorganic acid.

21. The method for regenerating waste graphite negative electrode materials according to claim 20, characterized in that: The inorganic acid is at least one of hydrochloric acid, nitric acid and hydrofluoric acid, wherein the concentration of the acid is 1-8M.

22. The method for regenerating waste graphite negative electrode materials according to claim 20, characterized in that: In the acid-treated solution, the inorganic acid is a ternary composite acid comprising hydrochloric acid, nitric acid and hydrofluoric acid; wherein the concentration of hydrofluoric acid is 1-2 mol / L, the concentrations of hydrochloric acid and nitric acid are 2-4 mol / L, the pickling temperature is 40-60°C, and the amount of hydrogen peroxide added is 0.01-0.5 mol / L.

23. The method for regenerating waste graphite negative electrode materials according to claim 20, characterized in that: In the acid-treated solution, the concentration of hydrogen peroxide is 0.01-0.5 mol / L.

24. The method for regenerating waste graphite negative electrode materials according to claim 20, characterized in that: The acid treatment time is 1~3h.

25. The method for regenerating waste graphite negative electrode materials according to any one of claims 1 to 24, characterized in that: The method further comprises step (3): coating the graphite negative electrode material obtained in step (2) with a carbon source to obtain a carbon-coated precursor, and then performing a carbonization treatment to obtain an amorphous carbon-coated graphite negative electrode material.

26. The method for regenerating waste graphite negative electrode materials according to claim 25, characterized in that: In step (3), the graphite negative electrode material obtained in step (2) is mixed with a carbon source in a molten state, and is pre-treated under negative pressure, then treated under positive pressure, and then cooled and solidified to obtain a carbon-coated precursor.

27. The method for regenerating waste graphite negative electrode materials according to claim 26, characterized in that: The weight ratio of the treated product in step (2) to the carbon source is 10-50:

1.

28. The method for regenerating waste graphite negative electrode materials according to claim 26, characterized in that: The carbon source is asphalt with a softening point of 65-90°C.

29. The method for regenerating waste graphite negative electrode materials according to claim 26, characterized in that: The temperature during negative pressure and positive pressure treatment is 150~200℃.

30. The method for regenerating waste graphite negative electrode materials according to claim 26, characterized in that: The negative pressure is less than or equal to 80mbar, and the positive pressure is 0.1-0.5Mpa.

31. The method for regenerating waste graphite negative electrode materials according to claim 26, characterized in that: The holding time for negative pressure and positive pressure is 5-10 minutes respectively.

32. The method for regenerating waste graphite negative electrode materials according to claim 25, characterized in that: In step (3), carbonization is carried out under a protective atmosphere.

33. The method for regenerating waste graphite negative electrode materials according to claim 25, characterized in that: The carbonization temperature is 1000~1300℃.

34. The method for regenerating waste graphite negative electrode materials according to claim 25, characterized in that: The carbonization temperature is 1100~1200℃.

35. The method for regenerating waste graphite negative electrode materials according to claim 25, characterized in that: The carbonization time is 3~6h.

Citation Information

Patent Citations

  • Method for regenerating waste and old graphite anode materials

    CN102544629A

  • Method for preparing silicon-carbon composite material using negative electrodes of waste lithium-ion batteries and application

    WO2022179292A1